Kingdom of the Netherlands-Netherlands Antilles : Assessment of the Supervision and Regulation of the Financial Sector Volume II- Detailed Assessment of Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2004)
This detailed assessment of the observance of standards and codes in the financial sector of the Kingdom of the Netherlands-Netherlands Antilles reviews implementation of the Basel Core Principles for effective banking. Legal provisions are in place entrusting the Bank of the Netherlands Antilles (BNA) to regulate the insurance sector and designate it as the licensing authority. The BNA considered that asset quality issues were relevant primarily for domestic institutions and less for international banks in the Netherlands Antilles.